Evaluation of resistance to wheat stem rust and identification of resistance genes in wheat lines from Heilongjiang province - Qiujun Lin; Yue Gao; Xianxin Wu; Xinyu Ni; Rongzhen Chen; Yuanhu Xuan; Tianya Li (PeerJ, 2021)
Wheat stem rust, caused by Puccinia graminis f. sp. tritici, (Pgt) is a devastating disease in wheat production. The disease has been effectively controlled since the 1970s due to the widespread use of the Sr31 resistance gene. However, Sr31 has lost its effectiveness following the emergence and spread of the Ug99 race variants. Therefore, there is an urgent global effort to identify new germplasm resources effective against those races. In this study, the resistance to Pgt of 95 wheat advance lines from Heilongjiang Province was evaluated using three predominant races of Pgt, 21C3CTTTM, 34C0MKGSM, and 34C3MTGQM, in China at the seedling and adult plant stage. The presence of 6 Sr genes (Sr2, Sr24, Sr25, Sr26, Sr31, and Sr38) was evaluated using linked molecular markers. The results showed that 86 (90.5%) wheat lines had plant stage resistance to all three races. Molecular marker analysis showed that 24 wheat lines likely carried Sr38, 15 wheat lines likely carried Sr2, 11 wheat lines likely carried Sr31, while none of the wheat lines carried Sr24, Sr25, or Sr26. Furthermore, six out of the 95 wheat lines tested carried both Sr2 and Sr38, three contained both Sr31 and Sr38, and two wheat lines contained both Sr2 and Sr31. Wheat lines with known Sr genes may be used as donor parents for further breeding programs to provide resistance to stem rust.